Narrative Closure in Honor Killing Cases: How Judgments Stabilise Meaning, Eliminate Ambiguity, and Produce Sentencing Certainty - Zul Khaidir Kadir (Punggawa Law Review, 2026)
Honour killing judgments were often read as straightforward applications of homicide doctrine, yet the written reasons frequently performed additional work by stabilising contested meanings. This article examined how criminal courts produced narrative closure in honour killing cases by narrowing interpretive possibilities, fixing causal chains, and translating a settled story into sentencing certainty. A qualitative judicial decision analysis was conducted using a structured protocol that segmented judgments into factual narrative, evidentiary assessment, legal qualification, and sentencing reasons, then mapped closure across causal, moral, evidentiary, and sentencing dimensions. The analysis found that judgments commonly elevated a reputational “trigger” into the dominant cause, embedded respectability scripts that redistributed moral weight, and constructed credibility hierarchies that converted honour claims into neutral-seeming facts. These moves frequently enabled mitigation drift, in which honour-based frames softened perceived agency without explicit doctrinal endorsement. The study concluded that relevance boundaries in judicial reason-giving were necessary to prevent honour narratives from operating as implicit excuses while preserving their probative value for planning, coercive control, and collective enforcement.